2022
DOI: 10.1098/rsos.220428
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage targeting of nitazoxanide-loaded transethosomal gel in cutaneous leishmaniasis

Abstract: Topical delivery is preferable over systemic delivery for cutaneous leishmaniasis, because of its easy administration, reduced systemic adverse effects and low cost. Nitazoxanide (NTZ) has broad-spectrum activity against various parasites and has the potential to avoid drug resistance developed by enzymatic mutations. NTZ oral formulation is associated with severe dyspepsia and stomach pain. Herein, NTZ-transethosomes (NTZ-TES) were prepared and loaded into chitosan gel (NTZ-TEG) for topical delivery. NTZ-TES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The nitazoxanide-treated group presented a lower average body weight than all of the other groups, most likely due to some side effects of the drug (anorexia, diarrhea, and nausea) that probably caused a lower feed intake and weight loss, or a direct catabolic effect of the drug, since some studies showed that although it can be well tolerated due to its good safety profile, it may be associated of adverse reactions, especially when prolonged and increased oral doses are administered [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nitazoxanide-treated group presented a lower average body weight than all of the other groups, most likely due to some side effects of the drug (anorexia, diarrhea, and nausea) that probably caused a lower feed intake and weight loss, or a direct catabolic effect of the drug, since some studies showed that although it can be well tolerated due to its good safety profile, it may be associated of adverse reactions, especially when prolonged and increased oral doses are administered [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suitable dilutions of the samples were prepared and analyzed using HPLC as discussed above for the quantification of RLX and the release graphs were drawn using Sigma plot software. Additionally, DD-Solver was used to check the best fitted release model [ 37 , 38 ].…”
Section: Characterization Of Rlx-pnpsmentioning
confidence: 99%
“…Still, the zeta potential value is increased, indicating stability and a threefold increase in EE, which may be due to reduced polarity by combining deoxycholate anion and drug cation. 37 Salem et al 1 and Khalid et al 38 study revealed that increasing surfactant concentration could cause a substantial decrease in the vesicle size due to interfacial tension being reduced by high surfactant levels covering the carrier surface. This Tween 80 effect results in its solubilizing property and inhibition of vesicle cohesion.…”
Section: Edge Activatormentioning
confidence: 99%